Solving Equations with indices

Easy

Medium

Difficult

Q1) \(8^{6 x -2} = 8^10\)
Q1) \(2^{2 x -10} = 2^6\)
Q1) \(2^{9x + 8} = 4^{6x + 9}\)
Q2) \(3^{2 x -4} = 3^8\)
Q2) \(8^{2 x -10} = 8^8\)
Q2) \(3^{4x + 9} = 9^{8x -2}\)
Q3) \(3^{5 x -2} = 3^3\)
Q3) \(4^{8 x -6} = 4^2\)
Q3) \(4^{10x + 10} = 1024^{7x -9}\)
Q4) \(9^{4 x -9} = 9^7\)
Q4) \(8^{5 x +3} = 8^8\)
Q4) \(3^{5x + 2} = 243^{2x -10}\)
Q5) \(8^{2 x -9} = 8^9\)
Q5) \(4^{4 x -8} = 4^4\)
Q5) \(4^{5x + 5} = 256^{2x -10}\)
Q6) \(2^{2 x +8} = 2^4\)
Q6) \(2^{3 x -10} = 2^5\)
Q6) \(5^{8x + 2} = 125^{4x -7}\)
Q7) \(4^{2 x +2} = 4^6\)
Q7) \(9^{5 x +3} = 9^8\)
Q7) \(4^{6x + 6} = 16^{10x -5}\)
Q8) \(7^{2 x -9} = 7^7\)
Q8) \(2^{5 x -6} = 2^9\)
Q8) \(2^{5x + 3} = 32^{10x + 6}\)
Q9) \(2^{3 x -10} = 2^8\)
Q9) \(6^{3 x +6} = 6^9\)
Q9) \(4^{6x + 3} = 1024^{10x -4}\)
Q10) \(4^{6 x -10} = 4^2\)
Q10) \(8^{9 x -4} = 8^5\)
Q10) \(5^{8x + 6} = 3125^{9x + 5}\)